The effect of stress and organizational culture on job satisfaction - Sutedja, Dewa Ayu Gladysia Sistadanta Kurnia Dewi; Paudie, Mohamad Maulidin Ravie; Sudama, I Made (Privietlab, 2026)
Workplace stress has become an inevitable phenomenon in modern organizations. As task complexity, competition, and performance expectations increase, many workers experience prolonged stress. This phenomenon significantly impacts employees' mental and physical health, reduces their concentration, and increases the risk of burnout. Organizational culture can be likened to the philosophy, ideology, values, beliefs, and norms that bind an organization. An organizational culture that has been internalized and accepted by each member can impact employee job satisfaction in the company. This systematic literature review is compiled based on the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) from research related to the influence of stress and organizational culture on job satisfaction. Job stress significantly and negatively affects job satisfaction and organizational commitment. The higher the level of stress, the lower the individual's positive evaluation of the work environment, relationships between colleagues, and the rewards they receive. A positive organizational culture increases job satisfaction, strengthens relationships between employees, and encourages the creation of a harmonious work atmosphere. Conversely, a weak or poor organizational culture can decrease employees’ job satisfaction.